2014
DOI: 10.1186/1472-6882-14-388
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine after the completion of hospital treatment for colorectal cancer: findings from a questionnaire study in Denmark

Abstract: BackgroundLittle is known about the use of complementary and alternative medicine (CAM) for colorectal cancer, despite the high incidence of colorectal cancer and the frequency of CAM use for cancer-related symptoms. This is the first Danish study to examine the use of CAM by individuals who completed hospital treatment for colorectal cancer.MethodsIn 2011–12, a pragmatic trial on energy healing as rehabilitation after colorectal cancer was conducted in Denmark with participants who had completed cancer-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 22 publications
5
45
2
1
Order By: Relevance
“…Most studies focused on the use of CAM regarding only 1 cancer entity [7,8,9,10,11,12,13,17,18]. Only a few recent studies analyzed the use of CAM in all cancer entities [3,4,5,6], with different percentages of users from 32-95%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies focused on the use of CAM regarding only 1 cancer entity [7,8,9,10,11,12,13,17,18]. Only a few recent studies analyzed the use of CAM in all cancer entities [3,4,5,6], with different percentages of users from 32-95%.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers vary depending on the cultural background the study was conducted in [3,7] and the cancer entities examined[8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…5 women with breast cancer diagnosis reported CAM use 12 to 16 weeks post-surgery; 9 and 49% of patients who had recently completed conventional colorectal cancer treatment reported some form of CAM treatment in the past month. 10 Although updated prevalence data for CAM use for all categories of patients with cancer in Denmark are lacking, these two surveys suggest CAM use among Danish patients with cancer may be comparable to patients in other countries. CAM is used by both men and women, and in different sub-groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…23 Although no epidemiological studies report on use of homeopathy among patients with cancer in Denmark, similar characteristics have been found in Danish breast and colorectal cancer CAM users. 9,10 Results of the German study suggested that the homeopathy group had a longer disease history than patients with cancer receiving conventional treatment, indicating that the two groups entered the study at different disease phases. Their quality of life, levels of anxiety, depression and fatigue scores were, however, comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little is known about CIH use in Hispanics with a diagnosis of colorectal cancer (CRC). Existing data from several international studies show that CIH use among patients with CRC ranges in prevalence between 20% and 50%; 27 , 40–42 however, the two U.S. studies suggest inconsistent findings, with use at 31% and 75%. 43 , 44 To better understand the prevalence and patterns of CIH use among Hispanic patients with CRC living in the United States, this large population-based study in California sought to describe the CIH products and techniques used by Hispanic adults.…”
Section: Introductionmentioning
confidence: 99%